2021
DOI: 10.1101/2021.01.16.426936
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

ORFik: a comprehensive R toolkit for the analysis of translation

Abstract: ABSTRACT•BackgroundWith the rapid growth in the use of high-throughput methods for characterizing translation and the continued expansion of multi-omics, there is a need for back-end functions and streamlined tools for processing, analyzing, and characterizing data produced by these assays.•ResultsHere, we introduce ORFik, a user-friendly R/Bioconductor toolbox for studying translation and its regulation. It extends GenomicRanges from the genome to the transcriptome and implements a framework that integrates d… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
3

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 58 publications
0
9
0
Order By: Relevance
“…Genome annotations (including ORFs, according to Stern-Ginossar et al, 2012 35 ) were transferred to the Towne var-S genome with metablastr 59 and Liftoff 60 . Data evaluation, comparison of the transcripts, assessing their coding potentials, calculating their Kozak sequence score, carrying out ORF predictions and BLAST comparisons and generating visualizations were carried out with the following R packages: ORFik 61 , Gviz 62 and tidygenomics 57,63 using custom R scripts. Promoter elements and PASs were searched with https:// github.…”
Section: Data Validationmentioning
confidence: 99%
“…Genome annotations (including ORFs, according to Stern-Ginossar et al, 2012 35 ) were transferred to the Towne var-S genome with metablastr 59 and Liftoff 60 . Data evaluation, comparison of the transcripts, assessing their coding potentials, calculating their Kozak sequence score, carrying out ORF predictions and BLAST comparisons and generating visualizations were carried out with the following R packages: ORFik 61 , Gviz 62 and tidygenomics 57,63 using custom R scripts. Promoter elements and PASs were searched with https:// github.…”
Section: Data Validationmentioning
confidence: 99%
“…The alignments were sorted and indexed with samtools 60 version 1.11, and reads that mapped to more than one location in the genome were discarded. uORFs were computationally identified using the R 55 package ORFik 61 . uORFs were identified using the pattern (ATG|TTG|CTG-3n-TAA|TAG|TGA), since translated uORFs can initiate on non-canonical start codons [62][63][64] .…”
Section: Identifying Translated Upstream Open Reading Framesmentioning
confidence: 99%
“…uORFs were computationally identified using the R(59) package ORFik (65). uORFs were identified using the pattern (ATG|TTG|CTG-3n-TAA|TAG|TGA), since translated uORFs can initiate on non-canonical start codons (66)(67)(68).…”
Section: Identifying Translated Upstream Open Reading Framesmentioning
confidence: 99%
“…Although it is challenging to characterize sORFs and to determine their potential functional role, several studies have now demonstrated the importance of sORFs in different cellular mechanisms (Zacharias et al, 2012;Zhang et al, 2018;Qin et al, 2018;Zheng et al, 2019b) and in the regulation of CDS translation (Calvo et al, 2009;van Heesch et al, 2019). While many of these sORFs function through their interaction with the ribosome and the resulting regulatory effect this enacts, some sORFs can also encode functional peptides.…”
Section: Introductionmentioning
confidence: 99%
“…Further examples of SEPs and their function is discussed in the last section of this review. Briefly, one can divide sORFs into different categories depending on their characteristics and the available evidence: 1) non-translated sORFs or those with no evidence of translation, simply defined from the genomic sequence (Young et al, 2015) 2) sORFs that are translated, possibly resulting in SEPs (van Heesch et al, 2019;Loughran et al, 2020) 3) sORFs and/or SEPs with a known function (Zacharias et al, 2012;Zhang et al, 2018;Qin et al, 2018;Zheng et al, 2019b;Cloutier et al, 2020). Taken together, this reflects a diversity of sORFs in both healthy and disease conditions and argues for a need to characterize them.…”
Section: Introductionmentioning
confidence: 99%